The war between right and might : based on Ekadasanipata, a Dharma jataka - Vajiravudh, King of Siam, 1881-1925 (Book Development Centre, Dept. of Curriculum and Instruction Development, Ministry of Education, 1999)
Based on a Buddhist Jataka story.